Indian immigration into Natal (1860-1872) - Thompson, Leonard Monteath; Lombard, P. J.1929-; Kistner, Wolfram; Venter, P. J.(Pieter Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thompson's contribution originally approved as M.A. thesis at the University of South Africa.